Gastrointestinal Nematodes Parasites Of Goats (Capra Aegagrus Hircus) In Merbok, Kedah, Malaysia: Studies Of Anthelmintic Efficacy Of Selected Plants, Prevalence And Nature Of Infection - Firuz, Fatin Amirah (2018)
Anthelmintic resistance of gastrointestinal nematodes (GIN) is a potentially costly problem that affected the livestock industries worldwide. The emergence of resistance urges the researchers to come out with an eco-friendly anthelmintic based on medicinal plants. Preliminary secondary metabolite screening by using gas chromatography and mass spectrum (GC-MS) and high – performance liquid chromatography (HPLC) were done for three plants crude extract; Azadiracta indica, Clinicantus nutans and Polyalthia longifolia. Few secondary metabolites focusing on sugar believed to boost the immunostimulant were d-mannose for neem and D-Frutose, 3-O-methyl-, 3-O-Methyl-d-glucose and glucose for ashoka. D-Allose was found in all three plant extracts. For HPLC few constituents identified were fructose, galactose, glucose and rhamnose. In addition, phytochemical analysis was conducted to investigate the presence of alkaloids, flavonoid, tannins, saponin, triterpenes and steroids. The phytochemical constituents of all three plants were shown to exhibit ethnoveterinary properties as it caused paralysis and death of third stage larvae in the larval migration inhibition assay and larval motility assay. An in vivo study was carried out from May to July 2016 to evaluate the efficacy of between selected plants aqueous extract and anthelmintic drugs (albendazole and ivermectin).